Combining BRAF inhibition with oncolytic herpes simplex virus enhances the immune-mediated antitumor therapy of BRAF-mutant thyroid cancer. Issue 2 (5th August 2020) - Crespo-Rodriguez, Eva; Bergerhoff, Katharina; Bozhanova, Galabina; Foo, Shane; Patin, Emmanuel C; Whittock, Harriet; Buus, Richard; Haider, Syed; Muirhead, Gareth; Thway, Khin; Newbold, Kate; Coffin, Robert S; et al.
Abstract : Background: The aggressive clinical behavior of poorly differentiated and anaplastic thyroid cancers (PDTC and ATC) has proven challenging to treat, and survival beyond a few months from diagnosis is rare. Although 30%–60% of these tumors contain mutations in the BRAF gene, inhibitors designed specifically to target oncogenic BRAF have shown limited and only short-lasting therapeutic benefits as single agents, thus highlighting the need for improved treatment strategies, including novel combinations. Methods: Using a BRAF V600E -driven mouse model of ATC, we investigated the therapeutic efficacy of the combination of BRAF inhibition and oncolytic herpes simplex virus (oHSV). Analyses of samples from tumor-bearing mice were performed to immunologically characterize the effects of different treatments. These immune data were used to inform the incorporation of immune checkpoint inhibitors into triple combination therapies. Results: We characterized the immune landscape in vivo following BRAF inhibitor treatment and detected only modest immune changes. We, therefore, hypothesized that the addition of oncolytic virotherapy to BRAF inhibition in thyroid cancer would create a more favorable tumor immune microenvironment, boost the inflammatory status of tumors and improve BRAF inhibitor therapy. First, we showed that thyroid cancer cells were susceptible to infection with oHSV and that this process was associated with activation of the immune tumor microenvironment in vivo. Next, we showed improved therapeutic responses when combining oHSV and BRAF inhibition in vivo, although no synergistic effects were seen in vitro, further confirming that the dominant effect of oHSV in this context was likely immune-mediated. Importantly, both gene and protein expression data revealed an increase in activation of T cells and natural killer (NK) cells in the tumor in combination-treated samples. The benefit of combination oHSV and BRAF inhibitor therapy was abrogated when T cells or NK cells were depleted in vivo. In addition, we showed upregulation of PD-L1 and CTLA-4 following combined treatment and demonstrated that blockade of the PD-1/PD-L1 axis or CTLA-4 further improved combination therapy. Conclusions: The combination of oHSV and BRAF inhibition significantly improved survival in a mouse model of ATC by enhancing immune-mediated antitumor effects, and triple combination therapies, including either PD-1 or CTLA-4 blockade, further improved therapy.